Dealing with gender-related challenges: A perspective of Zimbabwean women in the practice of law - Farai Maunganidze (Taylor & Francis Group, 2020)
Women in legal practice in Zimbabwe are subjected to cultural and structural restrictions in the cause of their work. In this context, the paper argues that women are not passive recipients of these challenges but come up with mechanisms to cushion themselves. The paper investigates the strategies employed by women as they negotiate these debilitating factors. Qualitative in-depth interviews were used with 46 participants who included 38 women and 5 men who were both in practice. Furthermore, three key informants were interviewed, one from the Law Society of Zimbabwe (LSZ) and two from the Zimbabwe Women Lawyers Association (ZWLA). The study demonstrates four broad strategies, namely, pulling out, conceding, social investment and going against the tide. Findings suggest that due to socio-cultural and structural constraints, the strategies are overwhelmingly maintaining male hegemonic tendencies and discriminatory practices in law firms. Therefore, there is need for all stakeholders including the professional body, law firm partners, men in practice and spouses to work together if women and men are ever going to have an equal operating environment in the practice of law in Zimbabwe.